2015
DOI: 10.1371/journal.pone.0116004
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Metallothionein Isoforms in Terrestrial Snail Embryos Reflects Early Life Stage Adaptation to Metal Stress

Abstract: The aim of this study was to analyze the expression of three metallothionein (MT) isoform genes (CdMT, CuMT and Cd/CuMT), already known from adults, in the Early Life Stage (ELS) of Cantareus aspersus. This was accomplished by detection of the MT isoform-specific transcription adopting Polymerase Chain Reaction (PCR) amplification and quantitative Real Time (qRT)-PCR of the three MT genes. Freshly laid eggs were kept for 24 hours under control conditions or exposed to three cadmium (Cd) solutions of increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…It will also be of interest to study the effects of cadmium on specific genes in gastropods. In this context, the Cd-selective metallothionein ( Cd-MT ) gene deserves particular consideration since it can be activated by dietary Cd levels as low as 2 mg/L [ 54 , 55 ] and is generally inducible, unlike constitutively expressed genes with housekeeping functions [ 56 ]. The Cd-MT gene contains CG sites [ 57 ], but there is no information available about their methylation status.…”
Section: Discussionmentioning
confidence: 99%
“…It will also be of interest to study the effects of cadmium on specific genes in gastropods. In this context, the Cd-selective metallothionein ( Cd-MT ) gene deserves particular consideration since it can be activated by dietary Cd levels as low as 2 mg/L [ 54 , 55 ] and is generally inducible, unlike constitutively expressed genes with housekeeping functions [ 56 ]. The Cd-MT gene contains CG sites [ 57 ], but there is no information available about their methylation status.…”
Section: Discussionmentioning
confidence: 99%
“…The studies demonstrated that pathological changes typical for Cd toxicity, specifically in the midgut gland, include an increased number of excretory cells with residual bodies (lipofuscin granules), programmed cell death, the disruption of mitochondrial membranes, and inflammation (Chabicovsky et al 2004 ; Hödl et al 2010 ; Amachree et al 2013 ; Sheir et al 2013 ). These alterations are thought to occur at Cd concentrations exceeding the capacity of metallothionein (MT), a low-molecular weight Cd-binding protein which is responsible for detoxification of the metal in the midgut gland of H. pomatia and other species (Dallinger et al 1997 ; Chabicovsky et al 2004 ; Hödl et al 2010 ; Baurand et al 2015 ). The non-MT-bound Cd ions are believed to generate reactive oxygen species and peroxidation of membrane lipids, thereby producing toxicity (Roesijadi et al 1997 ; Liu et al 2009 ; Amachree et al 2013 ).…”
mentioning
confidence: 99%
“…aspersus embryos [47](unpublished data). The CuMT gene is known to be up-regulated during Cu stress in adults [48].…”
Section: Bordeaux Mixturementioning
confidence: 97%